2017
DOI: 10.1111/eci.12793
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis chronic kidney disease correlates with increased risk of pyogenic liver abscess: a population-based cohort study

Abstract: Predialysis chronic kidney disease is associated with 1·5-fold increased risk of pyogenic liver abscess. There seem to be a synergistic effect on the risk of pyogenic liver abscess between predialysis chronic kidney disease and comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…All comorbidities were diagnosed based on ICD-9 codes. The validity of ICD-9 codes has been discussed in previous studies ( Hung et al, 2016 ; Lai et al, 2016 , 2017a , b ; Liao et al, 2016a , b , 2017a , b ; Shen et al, 2016 ; Wong et al, 2016 ; Lin C.M. et al, 2017 ; Hung et al, 2017 ).…”
Section: Methodsmentioning
confidence: 94%
“…All comorbidities were diagnosed based on ICD-9 codes. The validity of ICD-9 codes has been discussed in previous studies ( Hung et al, 2016 ; Lai et al, 2016 , 2017a , b ; Liao et al, 2016a , b , 2017a , b ; Shen et al, 2016 ; Wong et al, 2016 ; Lin C.M. et al, 2017 ; Hung et al, 2017 ).…”
Section: Methodsmentioning
confidence: 94%
“…Previous studies showed that cellular dysfunction of T cells and B cells, and phagocytic defect of neutrophils observed in chronic kidney disease might play the key roles in the involvement of developing herpes zoster 29‐31 . Some epidemiological studies showed that patients with predialysis chronic kidney were at risk of developing pneumonia, pyogenic liver abscess and pulmonary tuberculosis owing to declined immune functions 6‐8 . From a view of prevention medicine, vaccination and chemoprophylaxis are both strategies for primary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, impaired immune functions are commonly noted in patients with chronic kidney disease, including declined functions of T cells, B cells and neutrophils 4 . Therefore, patients with chronic kidney disease are at risk of various infectious diseases including pneumonia, pyogenic liver abscess and pulmonary tuberculosis 5‐8 …”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities potentially related to ischemic cerebrovascular disease before index date were identified as follows: alcohol-related disease, atrial fibrillation, chronic kidney disease, chronic obstructive pulmonary disease, coronary artery disease, hyperlipidemia, and hypertension. Based on the ICD-9 codes, the diagnosis validity of comorbidities was discussed in previous studies ( Lai et al, 2017a , b , c , d , e , f ; Liao et al, 2017e ; Lin et al, 2017b , c ).…”
Section: Methodsmentioning
confidence: 99%